Basil and Lettuce Microgreens Production in Low-Cost Hydroponic Installations, under Operational and Semi-Controlled Conditions - Teodor RUSU; Paula Ioana MORARU; Olimpia Smaranda MINTAȘ; Mihai Marcel CĂRBUNAR; Horia POP; Ioan Nicolae LUPUȚ (Bulletin of University of Agricultural Sciences and Veterinary Medicine Cluj-Napoca: Food Science and Technology, 2023)
Microgreens produced hydroponically at home, represent a solution of the future due to the advantages it has. The purpose of this research is to analyze certain elements relevant for the microgreens crop (basil and lettuce), simultaneously, in identical low-cost hydroponic platforms, in operational (common spaces) and semi-controlled conditions (plant growing tent). The obtained results were analyzed, both from the point of view of the growing conditions and the influence of light regimes, as well as the development of seedlings, production (fresh weight and dry weight) and quality (total phenolic) of the microgreens. In operational environmental conditions there is a higher variation of the environmental parameters, compared to the semi-controlled environment, but the oscillation of natural light seems to have a better influence on the development of microgreens. Internode length in operational environmental conditions varies for basil between 25.2-35.2 mm, for lettuce between 31.9-32.8 mm, and in semi-controlled environmental conditions, it varies for basil between 25.2-32.1 mm and for lettuce between 30.2-31.9 mm. In semi-controlled conditions, the average fresh weight production achieved by the two species (and four varieties) is 734.73 g m-2 for basil, 809.56 g m-2 for lettuce, and represents 823.74 g m-2 for basil, 777.61 g m-2 for lettuce in operational environmental conditions. The variability of the data recorded for total phenols is very high. Lettuce contains 98-107.33 mg kg-1, and basil 107.67-186.33 mg kg-1 total phenols. Feedback from these tests will be used for final validation of the low-cost hydroponic platform components.